Efficacy and safety of PD-1/L1 inhibitors as first-line therapy for metastatic colorectal cancer: a meta-analysis - Huang, Zhilong; Li, Chunyan; Huang, Yanping; Liang, Weiming; Tao, Haiyun (Frontiers in Immunology, 2024)
Objective To evaluate the efficacy and safety of PD-1/L1 inhibitors as first-line therapy in metastatic colorectal cancer(mCRC). Method Articles evaluating first-line PD-1/L1 inhibitors for mCRC were sought in four databases (Pubmed, Embase, Web of Science, and the Cochrane Library) from the inception of the databases until 11 November 2023. Meta-analyses were conducted to assess the rates of progression-free survival (PFS), overall survival (OS), complete response (CR), partial response (PR), stable disease (SD), progressive disease (PD), objective response rate (ORR), disease control rate (DCR), and grade ≥ 3 treatment-related adverse events (trAEs). Results Totally nine studies were included for meta-analysis. A subgroup analysis was performed based on mismatch repair(MMR) status and regimens. In patients diagnosed with mismatch repair-deficient(dMMR) mCRC who received PD-1/L1 inhibitors as their first-line treatment, the ORR was 0.54 (95% CI, 0.39 to 0.68), the median PFS was 53.2 months, the Grade≥ 3 TRAEs rate was 0.33(95% CI, 0.12 to 0.60) and the median OS was not determined. For patients with proficient mismatch repair (pMMR) mCRC who underwent a combined treatment of PD-1/L1 inhibitors, anti-VEGF monoclonal antibody and chemotherapy as their first-line therapy, the ORR was 0.62 (95% CI, 0.56 to 0.68), the median PFS was 10.1 months, the median OS was 26.7 months, and the Grade≥ 3 TRAEs rate was 0.59(95% CI, 0.39 to 0.77). Conclusion Our results revealed that the utilization of PD-1/L1 inhibitors as first-line therapy for dMMR mCRC yielded highly favorable outcomes, while maintaining an acceptable level of safety. Administering a combination of PD-1/L1 inhibitors, anti-VEGF monoclonal antibody, and chemotherapy as first-line treatment in patients with pMMR mCRC led to an improved ORR. However, there was no significant improvement in the long-term prognosis of the tumor. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024506196, identifier CRD42024506196.